COVID-19: High Risk Groups for COVID-19 and Challenges for Medical Universities - Ataniyazova, Oral A (Asian Pacific Journal of Environment and Cancer, 2020)
COVID-19 as a global pandemic created a new challenges to all countries in the world. Since 18 March 2020 there is cases of COVID-19 in Uzbekistan and in collaboration with WHO all medical society were prepared and trained under International standards in order provide adequate medical services to people. In order to better organize medical services to COVID-19 patients it is very important to clarify people with the high risk to COVID-19 and prioritize their treatment and prevention. Number of recent research and data was investigated and adopted to local condition of Uzbekistan. But still there is a group of people, which could be at the higher risk for COVID-19 than others. During decades the Republic of Karakalpakstan (in Uzbekistan) considered as the epicenter of the Aral Sea crisis with high level pollution. High level of Tuberculosis (TB), anemia, cancer and other diseases was discovered among local population. Our previous investigation has shown disorders in the immune, endocrine systems and other pathologies in women and children of this region. So the patients with TB and anemia, as well cancer and HIV considered the highest risk groups for COVID-19. The COVID-19 pandemic also affected education system in general. But it is especially very important to consider at the Higher medical education system in order to better organize education and practice for medical students, organize the activities of the teaching staff, improve capacity of the clinics, research and international collaboration.